2005
DOI: 10.1055/s-2005-873174
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Quercetin on the Mitochondrial NADH to NAD+Ratio in the Isolated Perfused Rat Liver

Abstract: It has been suggested that active forms of quercetin ( o-semiquinones) are able to oxidize NADH in mammalian cells. The purpose of this study was to investigate this proposition by measuring the beta-hydroxybutyrate to acetoacetate ratio as an indicator of the mitochondrial NADH/NAD (+) redox ratio in the isolated perfused rat liver. The NADH to NAD (+) ratio was reduced by quercetin; half-maximal reduction occurred at a concentration of 32.6 microM. Additionally, quercetin (25 to 300 microM) stimulated the Kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…It has been shown that quercetin can be transported and accumulated in the mitochondria preventing mitochondrial damage (Fiorani et al 2010), but it was also reported that active forms of this compound can oxidize mitochondrial as well as cytosolic NADH (Buss et al 2005;Gasparin et al 2003a;Chan et al 1999;Metodiewa et al 1999). This leads to a reduced NADH/NAD + ratio and shifts the cellular conditions to a more oxidized state.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown that quercetin can be transported and accumulated in the mitochondria preventing mitochondrial damage (Fiorani et al 2010), but it was also reported that active forms of this compound can oxidize mitochondrial as well as cytosolic NADH (Buss et al 2005;Gasparin et al 2003a;Chan et al 1999;Metodiewa et al 1999). This leads to a reduced NADH/NAD + ratio and shifts the cellular conditions to a more oxidized state.…”
Section: Discussionmentioning
confidence: 97%
“…This leads to a reduced NADH/NAD + ratio and shifts the cellular conditions to a more oxidized state. In the isolated perfused rat liver, it was shown that quercetin is stimulating TCA cycle activity which is probably caused by an increased mitochondrial NAD + availability (Buss et al 2005). Gasparin et al reported that quercetin inhibits lactate production and decreases cytosolic NADH/NAD + ratio (Gasparin et al 2003b).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, incubation with pyruvate, which acutely would increase the NAD + /NADH ratio, has been shown to increase SIRT1 abundance in Fao cells [11], and in the present study it increased SIRT1 and AMPK activity in HepG2 cells. Furthermore, we found that incubation with quercetin, a SIRT1-activating compound that has been shown to increase the acetoacetate to β-hydroxybutyrate ratio [22] (an indicator of the mitochondrial NAD + /NADH ratio), also increased AMPK activity. Collectively these data suggest a correlation between redox state and the activities of SIRT1 and AMPK; however, direct measures of cellular redox state, such as the lactate/pyruvate ratio and cellular NAD and NADH, are needed to establish this more definitively.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated perfused rat liver, quercetin stimulated the TCA cycle in the concentration range of 25-300 μM [71]. The authors suggested that the observed effect probably resulted from increased availability of NAD(+), as their study proved that the flavonol is able to act as a pro-oxidant in mammalian cells by participating in NADH oxidation.…”
Section: Class VII Mitocans: the Tricarboxylic Acid (Tca) Cycle-targementioning
confidence: 94%